2003
DOI: 10.1038/ng1148
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma mouse model implicates metabotropic glutamate signaling in melanocytic neoplasia

Abstract: To gain insight into melanoma pathogenesis, we characterized an insertional mouse mutant, TG3, that is predisposed to develop multiple melanomas. Physical mapping identified multiple tandem insertions of the transgene into intron 3 of Grm1 (encoding metabotropic glutamate receptor 1) with concomitant deletion of 70 kb of intronic sequence. To assess whether this insertional mutagenesis event results in alteration of transcriptional regulation, we analyzed Grm1 and two flanking genes for aberrant expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
369
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(387 citation statements)
references
References 18 publications
13
369
0
5
Order By: Relevance
“…Owing to the fact that the Grm1 'knock in' mouse model develops melanoma in the absence of UV radiation, 17,18 we decided to investigate whether the C allele of rs362962 could be a susceptibility genetic factor for GRM1 gene and melanoma susceptibility P Ortiz et al human melanoma tumours that do not appear to be dependent on sun exposure. Therefore, we selected those patients whose tumours were located on skin zones that are not usually exposed to sunlight such as the trunk and extremities, and who reported a low level of sun exposure, as described in the Materials and methods section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the fact that the Grm1 'knock in' mouse model develops melanoma in the absence of UV radiation, 17,18 we decided to investigate whether the C allele of rs362962 could be a susceptibility genetic factor for GRM1 gene and melanoma susceptibility P Ortiz et al human melanoma tumours that do not appear to be dependent on sun exposure. Therefore, we selected those patients whose tumours were located on skin zones that are not usually exposed to sunlight such as the trunk and extremities, and who reported a low level of sun exposure, as described in the Materials and methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Several years later, they demonstrated that the susceptibility to melanoma was due to an upregulation of the Grm1 gene expression. 18 Extending these studies to human melanomas, they also observed that the GRM1 gene was aberrantly expressed in 7 of 19 melanoma samples and 12 of 18 melanoma cell lines but not in normal human melanocytes or benign moles.…”
Section: Introductionmentioning
confidence: 99%
“…To test our hypothesis on the causative role of Grm1 in melanoma development, we generated another transgenic mouse line featuring Grm1 cDNA under the control of a melanocyte-specific dopachrome tautomerase promoter. As this transgenic model developed melanoma lesions very similar to the TG-3 model, we conclude that ectopic Grm1 expression alone is sufficient to induce spontaneous metastatic melanocytic neoplasia in vivo [10]. Further investigation identified mGluR1 expression in over 80% of human melanoma cell lines and 60% of human melanoma biopsies [11].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of various members of glutamate uptake/ receptors system in PCa is not known. We chose to study GRM1 expression in benign and malignant prostate tissues for the following reasons: (i) previous reports have indicated an oncogenic function and transforming ability for GRM1 in breast cancer and melanoma; [6][7][8] and (ii) our in vitro studies have proven GRM1 antagonists ability to induce apoptosis and significantly decreased PCa cells growth, migration and invasion. GRM1 expression was positive in basal cells of normal or benign prostatic hyperplasia (BPH), but weak or no expression in luminal acinar epithelial cells (Figure 1).…”
mentioning
confidence: 99%